IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DALAM MENINGKATKAN SIKAP TOLERANSI SISWA DI MAN 2 PROBOLINGGO - A. Faizul Mubarak; Fathor Rahman (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
The This study aims to describe in depth the implementation of the multicultural education process and analyse its impact on increasing the cultured tolerance of students at Madrasah Aliyah Negeri (MAN) 2 Probolinggo. Using a qualitative approach with a case study design, this study intensively examines how the school integrates multicultural values into the curriculum, learning activities, and the school environment. Data were collected through participatory observation, in-depth interviews with teachers, students, and principals, and analysis of related documents. The results showed that MAN 2 Probolinggo has made various efforts to create an inclusive learning environment, such as diversity-based curriculum development, extracurricular activities that encourage intercultural interaction, and the formation of a tolerant learning community. However, this study also identified several challenges faced, such as a lack of teacher training in implementing multicultural education and limited resources. Overall, this study highlights the important role of multicultural education in shaping students' character to be tolerant and respect diversity.